Técnica estadística para el control de calidad en prospección arqueológica. - Benito López, José Enrique; Valencia, José Luis; Almagro Gorbea, Martín; Alonso, Pablo; Martín Bravo, Ana M. (Complutum, 1997)
Sin resumen